Entrepreneurship: A Small Business Approach - Bruton Garry D; Bamford Charles E (NewYork : Mc Graw Hill Higher Education, 2010)
Entrepreneurship: A Small Business Approach takes a hands-on, problem-based learning approach that works through real problems faced by entrepreneurs and small business owners. Using real-world scenarios and exercises throughout, it puts the student in the roles of financial analyst, marketer, and business owner to find solutions. By drawing on the most current environmental conditions and solid research, Entrepreneurship provides students with the necessary foundation to design, start, and manage a small business.
Keywords: New Business Enterprises; Small business; Success in business